Experimental and numerical simulation study of Fe-based amorphous foil/Al-1060 composites fabricated by an underwater explosive welding method - Hanliang, Liang; Ning, Luo; Yanlong, Chen; Jiwei, Dong; Cheng, Zhai; Wei, Yang; Xiaojie, Li (Composite interfaces, 2021)
The joining of amorphous alloys and common metals has been hot subjects of abundant studies in recent years. Nevertheless, the crystallization and fracture of amorphous alloy are still big challenges during the joining process. This paper presents an innovatively underwater explosive welding method to weld the Fe-based amorphous foil and Aluminum 1060. The interfacial microstructure was characterized using the optical microscopy (OM), field emission scanning electron microscopy (FSEM) and micro X-Ray diffraction (XRD). Meanwhile, the underwater explosive welding process was simulated using smoothed particle hydrodynamics (SPH) method by ANSYS/AUTODYN software. The experimental results indicated that the Fe-based amorphous foil and Al plate were successfully welded without visible defects or cracks and an approximately 4 µm thick transition layer was formed at the joining interface. The elements mixed and formed intermetallic compounds at the transition layer. The simulation results verified the weldability of Fe-based amorphous foil and Al plates, which are in good agreement with experimental results.